Stabilitas Fisik Clay Mask Serbuk Biji Salak Wedi Sebagai Perawatan Kulit Bagi Pelaku Olahraga Rekreasi - Saputri, Romadhiyana Kisno; Al-Bari, Akhmad; Qoriati, Yani'; Nisak, Siti Khoirun; Safitri, Rina Alfianita (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2025)
Recreational sports participants have a high risk of experiencing skin problems due to ultraviolet radiation. This can be prevented by using cosmetics that act as photoprotection, such as clay masks with additional natural ingredients containing antioxidants, as skin care because the antioxidant content is able to prevent damage from free radicals and oxidative stress. This study aims to evaluate the physical stability of clay masks containing Wedi snake fruit seed powder and its potential as a skin care product for recreational sports participants. This study is an experimental study by creating 4 clay mask formulations with different concentrations of Wedi snake fruit seed powder. Clay mask stability was evaluated by different storage conditions (room temperature and refrigerator) and 6-cycle cycling tests with organoleptic measurements, pH, and irritation tests. The physical stability of clay masks containing Wedi snake fruit seed powder at room temperature storage was unstable because mould appeared on the 28th day, while it was stable when stored in the refrigerator and after refrigeration and after cycling tests. The presence of antioxidant activity in Wedi snake fruit makes clay masks containing Wedi snake fruit seed powder have the potential as a skin care product for recreational sports participants.